THE RESULTS OF COMPARATIVE ASSESSMENT OF MECHANIZED TECHNOLOGIES FOR GRAIN CROP CULTIVATION - V. I. Pakhomov; V. B. Rykov; S. I. Kambulov (Зерновое хозяйство России)
The article considers opportunities and gives the study of grain crop cultivated with various mechanized technologies under the conditions of insufficient and unstable humidity in the south of Russia. The steady trials have been carried out in the conditions of four field crop rotation with various tillage (moldboard, chisel), including a non-tillage variant. It has been established that the productivity of the experimental crops doesn’t tend to reduce with the non-tillage variant. The productivity of winter wheat is on 8% higher, peas productivity is on 15% higher and soybean productivity is on 37% higher compared with the use of conventional technology. The calculation of economic efficiency included determination of labour cost for one hectare of the arable land and for one hwt of the product, relative size of the capital investments, fuel consumption, operating costs of prime costs of manufacturing, etc. The use of non-tillage method for winter wheat production provides 1,000 hectares of arable land with the labor costs equal to 7213.6 people which is less on 11-21% compared with other technologies of winter wheat cultivation. This technology also reduces operating costs of prime costs of manufacturing to 5934,9 thousand rubles, fuel consumption to 36,1 t, which is less on 66-87% and 97-142 % respectively. The analysis of the system of costs shows that the costs of harvesting and plant care are almost identical for all considered technologies. Their principal difference of costs in fuel consumption, labour and money resources are determined with a complex of works under basic tillage. More than a half of operating costs is required for renovation that reveals high cost of the applied technical means and their low reliability (a small amortization period and large maintenance costs). Cost price of winter wheat production using a non-tillage method is 212,8 rubles per hwt, which is on 31-38% less in comparison with other cultivation technologies. Fuel consumption for spring barley production is 22,8 kg/ha, which is in 2,3-2,9 times less, than with various variants of conventional technologies.